1996
DOI: 10.1021/jo9505942
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Theoretical Studies on the Ring-Opening Modes of the Oxiranyl-, Aziridinyl-, Oxaziridinyl-, and Thiaranylmethyl Radical Systems

Abstract: Ab initio theoretical studies have been carried out on the oxiranyl-, aziridinyl-, oxaziridinyl-, and thiaranylmethyl radical systems and on the various possible conformations of the ring-opened heteroallyllic radical systems derived by ring opening of the first three systems. Previous theoretical studies on the ring opening of the oxiranylmethyl radical indicated that there is an overwhelming thermodynamic preference for the formation of the allyloxy radical over the formation of the (vinyloxy)methyl radical.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 9 publications
4
21
0
1
Order By: Relevance
“…While there is not much precedent for this mode of oxirane ring opening, it is rather similar to the welldocumented easy opening of oxiranylmethyl radicals. 14 Initial activation of an oxirane ring C-H bond is nearly as easy as methyl C-H activation. However, the subsequent C-O cleavage step has a prohibitively high barrier, making this a non-productive path.…”
Section: Dft Results For Oxirane Openingmentioning
confidence: 99%
“…While there is not much precedent for this mode of oxirane ring opening, it is rather similar to the welldocumented easy opening of oxiranylmethyl radicals. 14 Initial activation of an oxirane ring C-H bond is nearly as easy as methyl C-H activation. However, the subsequent C-O cleavage step has a prohibitively high barrier, making this a non-productive path.…”
Section: Dft Results For Oxirane Openingmentioning
confidence: 99%
“…The results of a recent calculational study carried out in the author's laboratories using various calculational methods including UHF, UMP2, MCSCF and employing many different split-level basis sets, including diffuse and polarization functions, on the oriranylmethyl-allyloxy-vinyloxymethyl 14 and other similarly related systems, 15 have indicated that geometry optimization calculations carried out at the UHF/6-31G ଙ level of theory followed by a single-point calculation at the QCISD(T)/6-31G…”
Section: Calculational Methodsmentioning
confidence: 99%
“…Indispensable information about the intermediates has been obtained from ab initio molecular calculations 15. 16 It was found that ring opening is exothermic for cleavage of both CO or CC bonds (Scheme ).…”
Section: Epoxide Oxetane and Aziridine Opening Through Generatiomentioning
confidence: 99%